Uma análise da perspectiva investigativa em material didático de ciências: coerência com a proposta pedagógica? - Oliveira, Andréia Aparecida Arruda de (Universidade Federal de São Carlos, 2014)
In the present research, we analized the pedagogical proposal from the learning system of SESI/SP, implanted in the educational web of the city of Araraquara, inland São Paulo. The four books to teach Science recommended by this proposal, used in the 6th to the 9th years (children aged 11 to 14, secondary school) were also analyzed both analyses were made by an investigative perspective. We searched to verify the consonance and coherence between the fundaments of the Proposal and what is executed in the books in terms of this proposal. The methodology used to orient this research was the analysis of the content. First, we investigated the fundaments of the Proposal in three dimensions: how the school curriculum is organized, what the teaching concept for Sciences is and how the investigative perspective works these topics made us capable to analyze the consonance between the Proposal and the activities of the books. Later, we characterized and quantified every each activity according to the categories of analysis created under the base of the aspects present in an investigative teaching approach. The created categories were: proposal of problems, formulation of hypotheses, observation of phenomena and objects, collecting data, interpreting data, elaboration of conclusions, systematization and socialization of the results. We also investigated the degree of openness provided by the book to the students, according to the previous categories. The data was organized through charts and the confection of evaluative cards, and when it was interpreted by these tools, it has allowed us to know better about the Science teaching approach transmitted in this material. The results indicate consonance between the Proposal and the material, although some considerations must be made about it.
Keywords: Educação; Proposta pedagógica; Material didático; Ensino de Ciências; Perspectiva investigativa; Pedagogical Proposal; Didactic material; Science teaching; Investigative perspective; CIENCIAS HUMANAS::EDUCACAO